The Influence of Online Stock Trading Platforms and Social Media Influencers on Investment Decisions Through Investment Interest (Study on Generation Y and Z in Pontianak) - Andika Leonardo Simangunsong; Harmono Harmono; Burhan Burhan (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of online stock trading platforms and social media influencers on investment decisions through investment interest among Generation Y and Z in Pontianak. The study applied a descriptive quantitative method involving 200 respondents selected using purposive sampling. Data were collected through online questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that online stock trading platforms have a positive and significant influence on investment interest, with a P-value of 0.000 (<0.05). Similarly, social media influencers also positively and significantly affect investment interest with a P-value of 0.000. Investment interest is proven to have a positive and significant relationship with investment decisions, with a P-value of 0.000. Online stock trading platforms also directly influence investment decisions with a P-value of 0.027 (<0.05). However, social media influencers do not have a significant direct influence on investment decisions, as indicated by a P-value of 0.163 (>0.05). Despite this, both online stock trading platforms and social media influencers indirectly influence investment decisions through investment interest, each showing a P-value of 0.000. The Q² value of 0.847 indicates that the model explains 84.7% of the data variation, demonstrating strong predictive relevance and confirming the importance of the studied variables in shaping investment decisions